Using Dose-Effect Relationship for Optimising Systemic Corticosteroid Dosage in Treatment of Inflammatory Bowel Diseases - O. P. Alekseeva; S. V. Krishtopenko; A. A. Alekseeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Estimation of an optimal corticosteroid (CS, prednisone) dosage for the remission induction in patients with ulcerative colitis (UC) and Crohn’s disease (CD) based on the construction of a dose-effect relationship during the first and second courses of therapy.Materials and methods. The study included 86 patients with moderate to severe active disease (61 with UC and 25 with CD) aged 18 to 65 years. To induce remission, all patients had the first course of prednisone at a starting dose of 30 to 60 mg/day, with a subsequent reduction. Prednisone was continued in a repeat course in 28 patients. The effect was evaluated past two weeks and at a time of complete withdrawal of prednisone using the generally accepted clinical response and remission criteria. The dose-effect relationship for prednisone was constructed using an original method. The method realises an adequate statistical transformation of primary clinical data in form of a quantitative expression of factual doses and registered alternative responses established with endpoint criteria into a visual efficacy function graph suitable for downstream analyses. The mean at each point was estimated with the regression kernel scoring method. The mean confidence intervals and significance values were estimated with the Student’s t-test.Results. The dose-effect relationship constructed upon completion of the first prednisone course is a graph showing the plateau point of the efficacy function as a statistical measure of character saturation and a clinical measure of the highest expected drug effect. This graph is referred to as the optimal clinically effective dose (OCED). The first induction prednisone course had the OCED estimates of 50.70 ± 0.65 (49.41÷51.98) mg (p = 0.05). A highest expected effect for this dose was obtained in the interval of 82.21 ± 8.23 (66.08÷98.33)% (p = 0.05). The repeat prednisone course had OCED values of 51.43 ± 1.55 (48.24÷54.61) mg (p = 0.05), with the expected effect of 40.02 ± 12.86 (13.59÷66.45)% (p = 0.05).Conclusion. In medium to severe UC and CD patients, the first induction prednisone course had OCED estimates of 50.70 ± 0.65 mg/day prescribed at the onset of therapy. The highest effect at this dose was 82%, and 18% of the patients did not respond to the prednisone treatment, accordingly. The repeat CS treatment had the same OCED values of 51.43 ± 1.55 mg/day, but a 42% lower expected effect compared to the first course. The effect did not exceed 40% suggesting its inadequacy in repeat CS treatments in this category of patients.